Persepsi Masyarakat terhadap Upaya Kepala Kelurahan sebagai Salah Satu Unsur Pelaksana Pemerintahan Kota Medan - Heri Kusmanto (Universitas Medan Area, 2015)
This paper reveals public perception of the efforts of village heads as one of the executing element Medan city administration in implementing Law No. 32 Year 2004 on Regional Government. Head of the village is already a way to implement Law Number 32 Year 2004 on Regional Government, this can be seen from the opinion of the people who have felt their development progress and success of the existing development, one example that people can feel the direct construction of facilities and road infrastructure has been improved, as well as some development flood management and handling of environmental cleanliness. Socialization conducted by the Head of the village in order to accelerate the construction of villages that have been run in accordance with what is expected by the public. Broad authority granted to the region with the issuance of Law No. 32 of 2004 on village heads are expected to reduce the gap and be able to improve the general well-being both at central and regional levels. Therefore, the regional autonomy of state power closer to the people will provide ample opportunity for the public to play an active role in regional development.